Urea cycle; oxidative phosphorylation 2 - Feigenson, Gerald W. (Henry Stewart Talks, 2020)
Electronic transport in Mitochondria (Complexes I to IV), H+ gradient in mitochondria and Chemiosmotic mechanism, ATP synthase
Reviewed at 2022/11/27